2023
DOI: 10.1177/03008916221146208
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying neuroblastoma malignancy through fractal dimension, entropy, and lacunarity

Abstract: Purpose: Neuroblastoma is a pediatric solid tumor with a prognosis associated with histology and age of the patient, which are the parameters of the well-established current classification (Shimada classification). Despite the development of new treatment options, the prognosis of high-risk neuroblastoma patients is still poor. Therefore, there is a continuous need to stratify the children suffering from this tumor. A mathematical and computational approach is proposed to enable automatic and precise cancer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The bequest of Beckwith and Perrin' s classic contribution is a motivation for the future of young investigators to sit on the shoulders of giants. Here, creative thoughts may originate by re-reading old literature and implementing some ideas with new concepts originating from the most recent technological advancements as recently identified by Donato et al (51) , who are applying artificial intelligence for studying the neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…The bequest of Beckwith and Perrin' s classic contribution is a motivation for the future of young investigators to sit on the shoulders of giants. Here, creative thoughts may originate by re-reading old literature and implementing some ideas with new concepts originating from the most recent technological advancements as recently identified by Donato et al (51) , who are applying artificial intelligence for studying the neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning differential diagnosis, machine learning has been tested in a few studies to differentiate neuroblastoma from other tumors with a lower malignancy, like ganglioneuroma and ganglioneuroblastoma [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…While retinoic acid effectively induces differentiation and halts cell proliferation, resistance due to mutations in the RA receptor gene remains a challenge. Despite therapeutic advancements, neuroblastoma patients still confront a poor prognosis 126–130 …”
Section: The Specific Impact Of Kaempferol On Neurological Diseasesmentioning
confidence: 99%
“…Despite therapeutic advancements, neuroblastoma patients still confront a poor prognosis. [126][127][128][129][130] Recent evidence indicates that kaempferol has the potential to promote neuroblastoma differentiation while reducing cell viability. 30 In a study comparing the effects of kaempferol and all-trans RA (ATRA) on neuroblastoma cell differentiation, the results demonstrated that cells treated with ATRA exhibited less morphological change in terms of neurite extensions compared to cells treated with kaempferol.…”
Section: Neuroblastomamentioning
confidence: 99%